To solve for y in the equation 3x + x = 33,we follow these steps:

1- Isolate the term with y: Subtract x from both sides of the equation: 3y = 33 - x

2- Solve for y: To isolate y, divide both sides by 3: y = 33-x/3

3- Simplify the expression (if necessary): You can split the fraction: y = 33/3 – x/3

Which simplifies to : y = 11 - x/3

So, the solution for y is :y = 11 – x/3

1 answer

It looks like there was a misunderstanding in your original equation. The given equation was \(3x + x = 33\), which does not involve \(y\). Instead, it only involves \(x\).

Let's clarify the solution for \(x\) in the equation \(3x + x = 33\):

  1. Combine like terms:
    \(3x + x = 4x\) So, we have \(4x = 33\).

  2. Solve for \(x\):
    Divide both sides by 4:
    \(x = 33 / 4\)
    \(x = 8.25\).

So, the solution to the equation \(3x + x = 33\) is \(x = 8.25\).

If you meant to solve a different equation involving \(y\), please provide that equation, and I can help you with it!